Book Review. Issue 2 (1st October 2019) - Beauregard, Mark
Collaborations Within and Between Dramatherapy and Music Therapy: Experiences, Challenges and Opportunities in Clinical and Training Contexts, Amelia Oldfield and Mandy Carr (eds) (2018) London: Jessica Kingsley Publishers, 256 pp., ISBN 978-1-78592-135-3, p/bk, $22.99; ISBN 978-1-78450-402-1, epub, $22.99